Juridical Analysis of the Division of Joint Property in Divorce Cases in Indonesia: Study of Decision No. 308/Pdt.G/2025/PA.Plk - Aulia Zahra, Nurul; Mahdiyani, Siti; Ya Ngoh, Burhan (Berasan: Journal of Islamic Civil Law, 2025)
This study aims to provide a juridical analysis of the division of joint property in divorce cases based on Decision Number 308/Pdt.G/2025/PA.Plk of the Palangka Raya Religious Court. The research focuses on the legal basis applied by the judge, the juridical considerations underlying the decision, and its conformity with the Marriage Law and the Compilation of Islamic Law (KHI). The method used is normative legal research with a case study approach, analyzing court decisions, legislation, Islamic legal doctrines, and family law literature. The findings reveal that the division of joint property is generally based on the principle of fairness, granting equal shares to husband and wife. In this case, however, the dispute arose because the defendant retained control over the property after the divorce, prompting the plaintiff to file a lawsuit with a request for a conservatoir beslag (security seizure). The proceedings led to mediation, which resulted in a peaceful settlement, and the lawsuit was subsequently withdrawn. Although the case ended amicably, the settlement lacks legal strength because the agreement was not formalized through a deed of settlement (akta perdamaian). The conclusion emphasizes that the mechanism of joint property distribution is not only governed by statutory law but also shaped by mediation as a dispute resolution tool that prioritizes fairness and consensus. Therefore, formal legitimacy through a deed of settlement is essential to ensure that a peacefully resolved case still carries binding legal force